Recellularization of a novel off-the-shelf valve following xenogenic implantation into the right ventricular outflow tract. - Ryan S Hennessy; Jason L Go; Rebecca R Hennessy; Brandon J Tefft; Soumen Jana; Nicholas J Stoyles; Mohammed A Al-Hijji; Jeremy J Thaden; Sorin V Pislaru; Robert D Simari; John M Stulak; Melissa D Young; et al. (PLoS ONE, 2017)
Current research on valvular heart repair has focused on tissue-engineered heart valves (TEHV) because of its potential to grow similarly to native heart valves. Decellularized xenografts are a promising solution; however, host recellularization remains challenging. In this study, decellularized porcine aortic valves were implanted into the right ventricular outflow tract (RVOT) of sheep to investigate recellularization potential. Porcine aortic valves, decellularized with sodium dodecyl sulfate (SDS), were sterilized by supercritical carbon dioxide (scCO2) and implanted into the RVOT of five juvenile polypay sheep for 5 months (n = 5). During implantation, functionality of the valves was assessed by serial echocardiography, blood tests, and right heart pulmonary artery catheterization measurements. The explanted valves were characterized through gross examination, mechanical characterization, and immunohistochemical analysis including cell viability, phenotype, proliferation, and extracellular matrix generation. Gross examination of the valve cusps demonstrated the absence of thrombosis. Bacterial and fungal stains were negative for pathogenic microbes. Immunohistochemical analysis showed the presence of myofibroblast-like cell infiltration with formation of new collagen fibrils and the existence of an endothelial layer at the surface of the explant. Analysis of cell phenotype and morphology showed no lymphoplasmacytic infiltration. Tensile mechanical testing of valve cusps revealed an increase in stiffness while strength was maintained during implantation. The increased tensile stiffness confirms the recellularization of the cusps by collagen synthesizing cells. The current study demonstrated the feasibility of the trans-species implantation of a non-fixed decellularized porcine aortic valve into the RVOT of sheep. The implantation resulted in recellularization of the valve with sufficient hemodynamic function for the 5-month study. Thus, the study supports a potential role for use of a TEHV for the treatment of valve disease in humans.